Health effects of the National Health Insurance Scheme (NHIS): A study among federal civil servants in Bayelsa State, Nigeria - Endurance Uzobo; Aboluwaji D Ayinmoro (Journal of Health and Social Sciences)
Introduction: This study aimed to analyze the level of satisfaction and health effects of the National Health Insurance Scheme (NHIS) among federal civil servants employed in Bayelsa State, Southern Nigeria. Methods: A cross-sectional survey was adopted using simple random sampling to recruit 337 federal employees living in the state. A structured questionnaire was used as data collection instrument to elicit socio-demographic information and types of services enjoyed under the scheme by the participants. Satisfaction levels and self-rated health were measured as continuous variables. Data was analysed using analysis of variance (ANOVA), multiple linear regression, and chi-square test. The level of statistical significance was set at P < 0.05. Results: Satisfaction levels and self-rated health differed significantly by demographic variables and types of services enjoyed by the participants (P < 0.05). Our findings showed that malaria treatment (β = 0.737, P < 0.05), prescriptions of drugs (β = 0.187, P < 0.05) and vaccinations (β = 0.422, P < 0.05) were good predictors of satisfaction levels and self-rated health status. Malaria treatment was associated with the highest satisfaction level (β = 0.737, P < 0.05) compared to other services enjoyed under the scheme. Discussion and Conclusion: In spite of the fact that most of the services under the scheme were associated with good self-reported health status and high satisfaction level by the participants, there are still some issues concerning supply of drugs and health facilities for federal employees living in Bayelsa State. The government and key stakeholders should ensure that NHIS provides adequate provisions of drugs, skilled health professionals and equipped healthcare facilities, as proper referral systems could mitigate the effects of health conditions affecting federal civil servants and promote the quality of health-care system.